Adaptasi Tradisi Begarehan di Era Modern: Pandangan Generasi Muda terhadap Pelestarian Budaya Lokal Kabupaten Lahat Sumatera Selatan : Begarehan - Malenda, Selly; camellia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Begarehan tradition is a form of customary practice in wedding ceremonies within the community of Lawang Agung Lama Village, Lahat Regency, South Sumatra, which embodies values of social solidarity, mutual cooperation, and local cultural identity. However, in the modern era, this tradition has undergone various changes due to modernization, social transformation, and shifts in the perspectives of the younger generation. This article aims to analyze the adaptation of the Begarehan tradition in the modern era and to examine the views of young people regarding the preservation of local culture. This study employs a qualitative approach, with data collected through interviews, observation, and documentation. The findings indicate that the younger generation still recognizes the Begarehan tradition as an important cultural heritage; however, its implementation has been simplified in terms of duration, forms of activities, and community participation. These adaptations are carried out to align the tradition with contemporary social, economic, and lifestyle conditions without eliminating its core values. Therefore, the preservation of the Begarehan tradition in the modern era depends not only on the continuity of customary practices but also on the awareness and active involvement of the younger generation in maintaining local cultural identity amid ongoing social change.